Nearness to Allah - Esmaeil Alikhani; Hajj Muhammad Legenhausen (Religious Inquiries, 2018)
Among the most paramount issues related to human self-understanding that are found in various cultures and ages are questions of the perfection of man and ultimate human happiness. In Islamic texts, ultimate human perfection is described as nearness to Allah. This article offers a brief review of the teachings of the Qur’ān on this topic and a sketch of the history of discussions of nearness to God in some of the Islamic sciences, particularly jurisprudence (fiqh), mysticism (‘irfān), theology (kalām), and (Islamic) philosophy (falsafah). Each of these areas is an arena for the expression of a distinctive perspective on nearness to God. With regard to each of them, we consider the following questions: Is it possible for human beings to approach God? If it is possible, what is the maximum extent of nearness to the divine? Can one become God or divine, or is proximity to God more limited? And, finally, what is the nature of this nearness, and what happens to a person when one approaches God? The answers found to these questions allow for a comparison of the four perspectives on nearness to God. The method used in this article is both rational and scriptural, although particular emphasis is given to the Qur’ān.